2022
DOI: 10.1057/s41599-022-01055-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of casino proximity on northeast urban communities: a literature review

Abstract: Gambling legalization, regulation, and casino proliferation in the United States have increased casino-gambling participation. The three A’s (accessibility, availability, and acceptability), known as ecological predictors of casino-gambling participation, have also been linked to the flood of casinos, including the influx of urban casinos in major metropolitan cities along the northeast corridor. Links between casino proximity, increased casino participation, and gambling-related problems are reported in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Other stakeholder interests are less well studied, but available evidence suggests that public health advocates may prefer locations away from population centers. Risks of problematic gambling appear to be related to gambling frequency (LaPlante & Shaffer, 2007; Potenza et al, 2019), and gambling frequency was demonstrated to be related to access convenience (O’Gilvie, 2022; Papineau et al, 2020; Philander, 2019; Philander et al, 2022; St-Pierre et al, 2014). Also, higher risks to socioeconomically disadvantaged populations tend to occur in urban areas, which may further motivate local public health stakeholders to encourage remote locations (Conway, 2015; Pérez et al, 2022).…”
Section: Related Literaturementioning
confidence: 99%
“…Other stakeholder interests are less well studied, but available evidence suggests that public health advocates may prefer locations away from population centers. Risks of problematic gambling appear to be related to gambling frequency (LaPlante & Shaffer, 2007; Potenza et al, 2019), and gambling frequency was demonstrated to be related to access convenience (O’Gilvie, 2022; Papineau et al, 2020; Philander, 2019; Philander et al, 2022; St-Pierre et al, 2014). Also, higher risks to socioeconomically disadvantaged populations tend to occur in urban areas, which may further motivate local public health stakeholders to encourage remote locations (Conway, 2015; Pérez et al, 2022).…”
Section: Related Literaturementioning
confidence: 99%
“…The hybrid racetrack casino, or racino, mainly offers electronic gaming machines (EGM) slot machines, while some only operate video lottery terminals (VLTs) based on the classi cation and regulations of the host state. Three major urban northeast corridor cities, NYC, Philadelphia, and Baltimore, host urban casinos, but only NYC hosts a racino, or a pari-mutuel casino, Resorts World New York City (RWNYC), which is attached to the Aqueduct Racetrack, and operates only VLTs regulated by The New York State Lottery Division (American Casino Guide, n.d.;O'Gilvie, 2022;Turner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Following years of relaxed gambling rules, regulations, and expansion, gambling outlets and opportunities have increased, such that casinos have opened in major metropolitan cities throughout the United States (Conway, 2015;Tolchard, 2015), making casino gambling also accessible and available. In addition, years of consistent gambling deregulation and casino expansions, introduced the urban casino (Conway, 2015;O'Gilvie, 2022) and expanded casino gambling to urban cities and local communities.…”
Section: Introductionmentioning
confidence: 99%